2015
DOI: 10.1016/j.matchemphys.2015.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of nickel antimony ferrospinels

Abstract: Spinel-type compounds of Fe-Ni-Sb-O system were synthesized as polycrystalline powders.The crystal and magnetic properties were investigated using X-ray and neutron powder diffraction, Mössbauer and X-ray absorption spectroscopy and magnetization measurements.The samples crystallize in the cubic system, space group Fd -3m. The distribution of cations between octahedral and tetrahedral sites was refined from the diffraction data sets using constraints imposed by the magnetic, Mössbauer and EDS results and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The variation of the magnetic moment formula unit as a function of doping concentration, x, is shown in Figure 14 for four different RE 3+ ions mentioned above. When x = 0.0, i.e., in the Gd 3 Fe 5 O 12 sample, the µ B ~16 agrees with the previous calculations [41,61,62]. With the increase in the x value, the total magnetic moment increases in the case of Dy 3+ doping.…”
Section: Theoretical Studysupporting
confidence: 86%
See 1 more Smart Citation
“…The variation of the magnetic moment formula unit as a function of doping concentration, x, is shown in Figure 14 for four different RE 3+ ions mentioned above. When x = 0.0, i.e., in the Gd 3 Fe 5 O 12 sample, the µ B ~16 agrees with the previous calculations [41,61,62]. With the increase in the x value, the total magnetic moment increases in the case of Dy 3+ doping.…”
Section: Theoretical Studysupporting
confidence: 86%
“…This discussion concludes that RE 3+ with a finite orbital angular momentum couple strongly with Fe 3+ sublattice moment via superexchange interaction. This behavior may be explained in terms of the temperature dependence of the magnetization of the three magnetic sublattices (dodecahedral, octahedral, and tetrahedral) balance each other [61,62]. Neel et al [41] reported that the magnetic properties of RE3Fe5O12 can be explained by assuming that the three sublattice ferrimagnetism is due to positive RE 3+ spin on dodecahedral sites, positive Fe 3+ spin on octahedral site, and negative Fe 3+ ion tetrahedral sites.…”
Section: Magnetic Propertiesmentioning
confidence: 99%